Translation Techniques Used in Indonesian Subtitle Text of the Main Character from Avengers: Endgame Movie Script - Mulyadi, Dandy; Juliansyah, Juliansyah; Fitriani, Nurul; Hariyana, Agustinus; Adi, Bambang Trisno (Universitas Pahlawan Tuanku Tambusai, 2023)
This study aims to analyze the types of translation techniques and find the most technique used by the translator in translating the utterances of Tony Stark as Iron Man to Steve Rogers as Captain America with the theory of Molina and Albir. Following a qualitative approach, this research employs a descriptive qualitative method to describe the translation techniques used. The research object in this study is the utterances of Tony Stark to Steve Rogers in Avengers: Endgame (2019) movie script. There are 56 translation techniques used with 12 types of translation techniques. They are, Linguistic compression used in 23 data (54%), Reduction used in 7 data (16,6%), Established Equivalent used in 5 data (11.9%), Variation used in 9 data (11,9%), Adaptation used in 5 data (11,9%), Calque used in 3 data (7,1%), Borrowing used in 3 data (7.1%), Compensation used in 2 data (4.7%), Literal translation used in 1 datum (2.3%), Modulation used in 1 datum (2.3%), Particularization used in 1 datum (2.3%), and Linguistic Amplification used in 1 datum(2.3%). Based on that, the study concludes that the most technique used is linguistic compression.